2008
DOI: 10.1162/jocn.2008.20.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Separable Forms of Reality Monitoring Supported by Anterior Prefrontal Cortex

Abstract: Reality monitoring refers to the process of discriminating between internally-and externallygenerated information. Two different tasks have often been used to assess this ability: memory for perceived vs. imagined stimuli; and memory for participant-vs. experimenter-performed operations, but it is not known whether these two reality monitoring tasks share neural substrates. The present study involved use of a within-subjects fMRI design to examine common and distinct brain mechanisms associated with the two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…Anterior PFC activation (or reduced deactivation) is frequently seen during context retrieval (e.g., Dobbins & Wagner, 2005;Simons et al, 2005aSimons et al, , 2005b; see also Mitchell & Johnson, 2009). The precise functional significance of anterior PFC for source memory is still under debate, but our results are consistent with the idea that medial anterior PFC mediates the retrieval of internally generated contextual details, such as the thoughts and associations produced during semantic encoding (e.g., Dobbins & Wagner, 2005;Simons et al, 2005aSimons et al, , 2005bSimons et al, , 2008. This hypothesis would explain why the source memory task was associated with less deactivation of anterior PFC than the item memory task, which would require retrieval of fewer details.…”
Section: Fmri Findings: Age-invariant Task Effectssupporting
confidence: 88%
“…Anterior PFC activation (or reduced deactivation) is frequently seen during context retrieval (e.g., Dobbins & Wagner, 2005;Simons et al, 2005aSimons et al, , 2005b; see also Mitchell & Johnson, 2009). The precise functional significance of anterior PFC for source memory is still under debate, but our results are consistent with the idea that medial anterior PFC mediates the retrieval of internally generated contextual details, such as the thoughts and associations produced during semantic encoding (e.g., Dobbins & Wagner, 2005;Simons et al, 2005aSimons et al, , 2005bSimons et al, , 2008. This hypothesis would explain why the source memory task was associated with less deactivation of anterior PFC than the item memory task, which would require retrieval of fewer details.…”
Section: Fmri Findings: Age-invariant Task Effectssupporting
confidence: 88%
“…Further, compared with non-human primates, rlPFC has a sparser spatial organization that may support greater interconnectivity [100]. The contribution of rlPFC to metacognitive commentary may be to represent task uncertainty in a format suitable for communication to others, consistent with activation here being associated with evaluating self-generated information [101,102], and attention to internal representations [103]. Such a conclusion is supported by recent evidence from structural brain imaging that 'reality monitoring' and metacognitive accuracy share a common neural substrate in anterior PFC [104].…”
Section: Neural Basis Of Metacognitive Accuracy (A) Studies Of Metamementioning
confidence: 88%
“…If so, it can be presumed that the neural processes regulating the emotional and behavioral responses to the stimuli-that is, the unconscious dynamic processes trigged by the stimuli-should be similar. Neuroscientific studies have in fact shown that while certain brain areas like the medial anterior (PFC) monitor whether a stimulus is internally or externally generated (Simons, Henson, Gilbert, & Fletcher, 2008), there is significant overlap between cortical areas that are activated regardless of whether a stimulus is generated internally or presented externally (Helmchen, Mohr, Erdmann, Binkofski, & Büchel, 2006;Stawarczyk, Majerus, Maquet, & D'Argembeau, 2011). For example, in the visual domain, imagery activates similar regions of visual cortex as retinal input does (Reddy, Tsuchiya, & Serre, 2010), and this has also been shown at the single-neuron level (Kreiman, Koch, & Fried, 2000).…”
Section: A Few Final Thoughtsmentioning
confidence: 99%